2019
DOI: 10.1186/s10194-019-0992-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of monoclonal antagonist antibodies on calcitonin gene-related peptide receptor function and trafficking

Abstract: BackgroundMonoclonal antibodies against calcitonin gene-related peptide (CGRP) or its receptor are efficacious for the prevention of migraine headaches. The downstream molecular mechanisms following ligand-receptor blockade by which these antibodies prevent CGRP signaling through CGRP receptors have not been demonstrated.MethodsHere we produced tool monoclonal functional antagonist antibodies against CGRP and its canonical receptor and developed a novel cellular model using fluorogen-activated protein technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…For example, membrane-bound CGRP receptors are known to internalize into endosomes after CGRP agonist stimulation. 8 , 9 Mechanistic studies in cellular and animal behavior assays have shown that these internalized CGRP receptors can continue to actively drive CGRP-mediated pain signals. 10 Given that the truncated peptide antagonist CGRP (8–37), conjugated to cholesterol for endosome-specific targeting, can suppress CGRP-mediated endosomal signaling and inhibit both cellular signals and animal pain responses, 10 it is possible that a differential ability for small molecules vs mAbs to enter cells and engage endosomal CGRP receptors may be a factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, membrane-bound CGRP receptors are known to internalize into endosomes after CGRP agonist stimulation. 8 , 9 Mechanistic studies in cellular and animal behavior assays have shown that these internalized CGRP receptors can continue to actively drive CGRP-mediated pain signals. 10 Given that the truncated peptide antagonist CGRP (8–37), conjugated to cholesterol for endosome-specific targeting, can suppress CGRP-mediated endosomal signaling and inhibit both cellular signals and animal pain responses, 10 it is possible that a differential ability for small molecules vs mAbs to enter cells and engage endosomal CGRP receptors may be a factor.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, neither receptor-targeted nor ligand-targeted CGRP mAbs are localized with internalized CGRP receptors in the presence of CGRP. 9 This may present a situation during migraine attacks (when CGRP levels are most elevated 11 ) in which the 2 agents have differential access to an endosome-bound CGRP-mediated pain signaling pathway and rimegepant might provide additional benefits to ongoing mAb therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the downstream molecular mechanisms following ligand-receptor blockade have not been clearly demonstrated. It's indicated that inactivating CGRP by anti-CGRP antibodies or blocking CGRP access to trigeminal neurons by anti-CGRP receptor antibodies, can interrupt CGRP-induced cAMP accumulation and inhibits CGRP receptor internalization [37].CGRP-related drugs have numerous advantages over existing conventional therapies, as they are designed specifically to act on the trigeminal pain system, along with more specific mechanisms of action and fewer adverse effects. CGRP receptor antagonists, such as ubrogepant and so on, are effective in relieving acute migraine headache, but the underlying liver toxicity restricts their long-term usage [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…However, the downstream molecular mechanisms following ligand-receptor blockade have not been clearly demonstrated. It's indicated that inactivating CGRP by anti-CGRP antibodies or blocking CGRP access to trigeminal neurons by anti-CGRP receptor antibodies, can interrupt CGRPinduced cAMP accumulation and inhibits CGRP receptor internalization [37] .CGRP-related drugs have numerous advantages over existing conventional therapies, as they are designed specifically to act on the trigeminal pain system, along with more specific mechanisms of action and fewer adverse effects. CGRP receptor antagonists, such as ubrogepant and so on, are effective in relieving acute migraine headache, but the underlying liver toxicity restricts their long-term usage [38,39] .…”
Section: Discussionmentioning
confidence: 99%